Circular business models in Ukraine - Terpugov, Oleksandr; Huliaiev, Vitalii; Yastremska, Larysa; Korniienko, Iryna; Anatskyi, Andrii; Kovalenko, Alla; Korniienko, Yurii; Filimonenko, Olha (Problems of Environmental Biotechnology, 2024)
Circular business models in Ukraine are considered